A Natural Experiment to Test the Effect of Sanction Certainty and Celerity on Substance-Impaired Driving: North Dakota’s 24/7 Sobriety Program - Midgette, Greg (Journal of quantitative criminology, 2021)
Objectives Evaluate the deterrent effect of a program that increases the certainty and celerity of sanction for arrestees ordered to abstain from alcohol and other drugs on substance-impaired driving arrests. Methods We examine participant compliance with orders to abstain from alcohol and other drug use via breathalyzer, body-worn continuous alcohol monitoring devices, transdermal drug patches, and urinalyses. We then evaluate the impact of the 24/7 Sobriety program on substance-impaired driving arrests. Using variation across counties in the timing of program implementation in North Dakota as a natural experiment, we use difference-in-differences fixed effects Poisson regressions to measure the program’s effect on county-level arrests for substance-impaired driving. Results Over half of participants ordered to abstain from substance use complete 24/7 Sobriety without a detected substance use event. At the county level, the program is associated with a 9% reduction in substance-impaired driving arrests after accounting for the impact of oil exploration in the Bakken region, law enforcement intensity, alcohol availability, whether the state’s large universities were in session, and socio-demographic characteristics. We find that the Bakken oil boom is associated with a 22% increase in substance-impaired driving arrests. Conclusions The results suggest frequent monitoring combined with increased sanction celerity deters substance use-involved crime. While the results are generally consistent with an earlier study of 24/7 Sobriety in another state, differences in the study outcome measures implementation choices across states make direct comparisons difficult. More can be learned by conducting randomized controlled trials that vary time on program, testing technology, and/or level of sanction.